2023
DOI: 10.1002/mrm.29593
|View full text |Cite
|
Sign up to set email alerts
|

Weakly supervised perivascular spaces segmentation with salient guidance of Frangi filter

Abstract: To develop a weakly supervised 3D perivascular spaces (PVS) segmentation model that combines the filter-based image processing algorithm and the convolutional neural network. Methods: We present a weakly supervised learning method for PVS segmentation by combing a rule-based image processing approach Frangi filter with a canonical deep learning algorithm Unet using conditional random field theory. The weighted cross entropy loss function and the training patch selection were implemented for the optimization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Gonzalez et al (2016a, 2016b, 2017), Wang et al (2016), and Ballerini et al (2018) all use scans from the Edinburgh Mild Stroke Studies. Other common data sources used are the Human Connectome Project (Shepehrband et al, 2019; Choi et al, 2020; Lan et al, 2023), the Lothian Birth Cohort 1936 (Ballerini et al, 2016, Wang et al, 2016), the Multi-Ethnic Study of Atherosclerosis (MESA) cohort (Rashid et al, 2023) and the Southall And BRent REvisited (SABRE) (Sudre et al, 2022, 4 participating studies). All these are well-known clinical and population studies with data available either by request to the data holders or through public databases, which facilitates comparability in the results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalez et al (2016a, 2016b, 2017), Wang et al (2016), and Ballerini et al (2018) all use scans from the Edinburgh Mild Stroke Studies. Other common data sources used are the Human Connectome Project (Shepehrband et al, 2019; Choi et al, 2020; Lan et al, 2023), the Lothian Birth Cohort 1936 (Ballerini et al, 2016, Wang et al, 2016), the Multi-Ethnic Study of Atherosclerosis (MESA) cohort (Rashid et al, 2023) and the Southall And BRent REvisited (SABRE) (Sudre et al, 2022, 4 participating studies). All these are well-known clinical and population studies with data available either by request to the data holders or through public databases, which facilitates comparability in the results.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 comparatively illustrates the distribution of sample sizes of the studies in this category. Dubost et al (2017Dubost et al ( , 2019aDubost et al ( , 2019bDubost et al ( , 2019cDubost et al ( , 2020 (Shepehrband et al, 2019;Choi et al, 2020;Lan et al, 2023), the Lothian Birth Cohort 1936 (Ballerini et al, 2016, the Multi-Ethnic Study of Atherosclerosis (MESA) cohort (Rashid et al, 2023) and the Southall And BRent REvisited (SABRE) (Sudre et al, 2022, 4 participating studies). All these are well-known clinical and population studies with data available either by request to the data holders or through public databases, which facilitates comparability in the results.…”
Section: Populations and Sample Sizesmentioning
confidence: 99%
“…There are other developed non‐invasive measures for estimating glymphatic function in humans other than the CSFF reported in this work, including the PVS load by segmentation and DTI‐ALPS. PVS segmentation can be performed on T2w but is only feasible for significantly enlarged ones in WM and the segmentation results vary across techniques and image quality 15,43 . DTI‐ALPS is a method that computes fluid diffusivity along PVS, which potentially reflects the glymphatic function 23,31,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 , 38 Varied research outcomes have linked PVS load to Aβ deposition, yet inconsistencies may arise from measurement sensitivity. 14 , 16 , 39 PVS enlargement may reflect CSF fluid stasis and reduced flow leading to overall deficits in glymphatic clearance 40 , 41 , 42 because PVS load segmentation depends on image (typically T2w) resolution and quality, 15 , 43 , 44 and only includes the visibly enlarged PVS surrounding periarteries in WM. 45 , 46 Our CSFF potentially overcomes these limitations by accounting for all parenchymal CSF water in PVS, including microscale PVS that traditional imaging might miss.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that enlarged PVS, obtained from a deep learning model, can be linked to the vascular amyloid-β accumulation [37]. CNN models have been showing promising results in the quantification and segmentation of PVS [38]. In addition, CNN models can also quantify PVS in four different brain regions: midbrain, hippocampi, basal ganglia and centrum semiovale [39], and these region-specific PVS can be influenced by sex, cardiovascular risk factors, APOE gene and imaging biomarkers [40 ▪▪ ].…”
Section: Applications Of Deep Learning Techniques In Neuroimaging For...mentioning
confidence: 99%